War Sum Up - Vandsø, Annette (Peripeti, 2017)
War Sum Up (2011) is not a ’Gesamtkunstwerk’ in which the separate parts melt seamlessly together and point towards a single joint narrative. Instead the visuals, the choreography, the lyrics and text, the costumes, and the music each live their separate lives.